Preschool quality and child development - Alison Andrew; Orazio P. Attanasio; Raquel Bernal; Lina Cardona Sosa; Sonya Krutikova; Marta Rubio-Codina (Institute for Fiscal Studies (IFS), 2019)
Global access to preschool has increased dramatically yet preschool quality is often poor. We use a randomized controlled trial to evaluate two approaches to improving the quality of Colombian preschools. We find that the first, which was rolled out nationwide and provides additional resources for materials and new staff, did not benefit children's development and, unintentionally, led teachers to reduce their involvement in classroom activities. The second approach additionally trains teachers to improve their pedagogical methods. We find this addition offset the negative effects on teacher behavior, improved the quality of teaching and raised children's cognition, language and school readiness.
Keywords: J13; I10; I20; H43; 330; early childhood development; preschool quality; childcare quality